Огуз — курган на ключовому роздоріжжі Скіфії (пошук Херсонеського сліду) - Болтрик, Ю.В. (Археологія і давня історія України, 2017)
Статтю присвячено встановленню факту існування давнього перехрестя шляхів поблизу кургану
Огуз. Аналіз наявної інформації дозволяє реконструювати маршрути, що пролягали в шести напрямках від кургана-гіганта. До відомого раніше
шляху з центру Скіфії на Боспор додається торговий транзит з хори Херсонесу до городищ Лісостепу. Маркерами тут правлять знахідки керамічної тари з Південного Понту і Херсонесу. Толчком в написании этой статьи послужило установление факта пересечения трех древних дорог близ кургана Огуз, среди них и средневекового Муравского шляха.
Детальный анализ археологической, картографической
и нарративной информации позволяет реконструировать
важный перекресток в центре степной области — между реками Днепр и Молочная. Удалось установить, что через
Огуз пролегали маршруты в шести направлениях. Помимо ранее известного пути из центра Скифии на Боспор,
удалось определить торговый транзит, который соединял
Херсонес и его хору с зоной лесостепных городищ. Маркерами тут служат пункты находок керамической тары из
южнопонтийских центров и Херсонеса. Доминирование импорта из Синопы и особенно из
Гераклеи в ІV — начале ІІІ вв. до н. э. возможно объяснить несколькими причинами. Первая из них — освоение краткого пути через Черное море в Западный Крым. Вторая — вероятное содействие скифского царя
Атея, взявшего под свой контроль поток товаров из Южного Понта. Третья — угасание либо переориентация
торговой активности полисов Эгейского моря (не исключено в связи с походом Александра Великого в Персию)
и экономическая активизация Гераклеи Понтийской. The establishment of the fact of crossing of three ancient
roads near Oguz kurhan was the impulse for writing this
article. The medieval Muravsky Shlyakh appeared to be
among those roads. A detailed analysis of archaeological,
cartographic and narrative information allows us to reconstruct
an important intersection in the center of the steppe
region between the Dnieper and Molochna rivers. It was
possible to establish that the routes in six directions ran
through Oguz. In addition to the previously known route
from the center of Scythia to Bosporus, it was possible to
determine the trade transit that connected Chersonesus and its choir with a zone of forest-steppe settlements. The
markers here are the points of finds of ceramic tare from the South-Pontian centers and Chersonesus.
The dominance of importation from Sinop and especially from Heraclea in the early 4th century BC can be explained
by several reasons. The first one is the development of a short way through the Black Sea to the Western Crimea.
The second is the probable assistance of Scythian king Athey, who took control of the flow of goods from South Pontus.
The third reason is the extinction or reorientation of the trading activity of the polies of the Aegean Sea (probably
in connection with the campaign of Alexander the Great to Persia) and the economic activation of Heraclea Pontus.